(untitled) (International Journal of Physiology, 2019)
Background Obesity is a huge problem because it leads to so many complications such as accelerated atherosclerosis, increased incidence of gallbladder disease, type-2 diabetes mellitus, insulin resistance and many carcinomas. One of the major causes for obesity is excess energy intake in food over energy expenditure. Excess weight gain is an important risk factor for hypertension. Hypertension target major organs of the body leading to coronary heart disease, cerebrovascular disease, kidney damage etc. The aim of the study was to investigate the effect of obesity (Body Mass Index(BMI) and Waist Circumference(WC)) on Blood pressure. Materials & Method Ethical committee approval was obtained before starting the study. For this study clinical history was recorded and physical examination including body weight, height, waist&hip circumferences were measured. Waist hip ratio(WHR)was calculated. Blood Pressure was recorded. Results Obesity was statistically associated with increase in both systolic & diastolic blood pressure. Conclusion This study revealed that abdominal obesity &increase in BMI were significantly associated with increase in blood pressure.